2017
DOI: 10.1093/neuonc/nox056
|View full text |Cite
|
Sign up to set email alerts
|

Intracystic interferon-alpha in pediatric craniopharyngioma patients: an international multicenter assessment on behalf of SIOPE and ISPN

Abstract: Intracystic interferon-alpha can delay disease progression and potentially offer a protracted time to definitive surgery or radiotherapy in pediatric cystic craniopharyngioma, yet demonstrates a favorable toxicity profile compared with other therapeutic modalities-important factors for this developing age group. A prospective, randomized international clinical trial assessment is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 46 publications
0
63
0
2
Order By: Relevance
“…Recently, interferon‐alpha is becoming increasingly favored as antiproliferative agent when delivered intracavitarily: a recent international, multicenter retrospective analysis on a wide cohort of pediatric patients, showed that the use of interferon‐alpha hindered the progression of tumor whether patients had received or not received previous treatment, with less morbidity.…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…Recently, interferon‐alpha is becoming increasingly favored as antiproliferative agent when delivered intracavitarily: a recent international, multicenter retrospective analysis on a wide cohort of pediatric patients, showed that the use of interferon‐alpha hindered the progression of tumor whether patients had received or not received previous treatment, with less morbidity.…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…For cystic CP, decompression via an intracystic catheter can be performed repeatedly when connected with an Ommaya reservoir. Mainly for recurrent single cystic CP, intracavitary instillation of sclerosing substances such as interferon alpha is a treatment of choice (16). Due to neurotoxicity in case of leakage, bleomycin instillation is obsolete (17).…”
Section: Neurosurgerymentioning
confidence: 99%
“…One such concerns the use of intracystic agents in patients with predominantly cystic craniopharyngioma. Smaller pilot studies have shown that repeated administration of intracystic interferon is associated with significant radiological improvement and sustained tumor control …”
Section: Epidemiologymentioning
confidence: 99%
“…Smaller pilot studies have shown that repeated administration of intracystic interferon is associated with significant radiological improvement and sustained tumor control. 82,83 BRAF inhibitors were proven effective in multiple adult cancer types harboring BRAF V600E. 84,85 As such, there are ongoing phase II studies in North America and Europe to evaluate the efficacy of BRAF and/or MEK inhibitors in children with LGG.…”
Section: Craniopharyngiomamentioning
confidence: 99%